2016
DOI: 10.1016/j.enbuild.2016.04.071
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and numerical study of an earth-to-air heat exchanger for air cooling in a residential building in hot semi-arid climate

Abstract: Experimental and numerical study of an earth-to-air heat exchanger for air cooling in a residential building in hot semi-arid climate, Energy and Buildings http://dx.doi.org/10. 1016/j.enbuild.2016.04.071 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 113 publications
(27 citation statements)
references
References 33 publications
0
20
0
Order By: Relevance
“…Khabbaz et al [ 10 ], discussed one of the renewable systems that provides better energy performance to HVAC system, which is the geothermal ground-air system. Geothermal systems can be developed by means of geothermal heat pumps, or as EAHX.…”
Section: Introductionmentioning
confidence: 99%
“…Khabbaz et al [ 10 ], discussed one of the renewable systems that provides better energy performance to HVAC system, which is the geothermal ground-air system. Geothermal systems can be developed by means of geothermal heat pumps, or as EAHX.…”
Section: Introductionmentioning
confidence: 99%
“…Their results showed that the saturation of soil by heat restricts the performance of the EAHE system, and this can be improved by running the system on winter days. Mohamed Khabbaz et al studied numerically and experimentally the EAHE connected to a residential building located in Morocco. Their experimental results showed that EAHX is a good semipassive system for air refreshment, as the recorded blown air temperature into the building is quasi‐constant at 25°C with air humidity around 40%, even though the outside temperature reaches more than 40°C.…”
Section: Introductionmentioning
confidence: 99%
“…In summer, EAHE systems cool the air that enters a ventilation unit [4]. Ground-coupled duct systems are researched extensively in countries with a subtropical climate, such as Brazil [5][6], a hot and arid climate [7], the hot and humid climate of Mexico in zones 2A and 3A [8], and in Italy [9], Turkey [10], and Egypt [11].…”
Section: Introductionmentioning
confidence: 99%